Exploring the Extent of Phosphorus and Heavy Metal Uptake by Single Cells of Saccharomyces cerevisiae and Their Effects on Intrinsic Elements by SC-ICP-TOF-MS - Qin, Wen; Stärk, Hans-Joachim; Müller, Susann; Reemtsma, Thorsten (Frontiers in Microbiology, 2022)
The effect of six heavy metals, namely, silver (Ag), lead (Pb), palladium (Pd), copper (Cu), nickel (Ni), and chromium (Cr), on phosphorus (P) uptake by yeast was investigated by single-cell analysis using inductively coupled plasma time-of-flight mass spectrometry (SC-ICP-TOF-MS). It was found that the P content in cells with 1.55 g L–1 P feeding after P starvation was increased by ∼70% compared to control cells. Heavy metals at 10 ppm, except Cu, had a negative impact on P accumulation by cells. Pd reduced the P content by 26% in single cells compared to control cells. Metal uptake was strongest for Ag and Pd (0.7 × 10–12 L cell–1) and weakest for Cr (0.05 × 10–12 L cell–1). Exposure to Cr markedly reduced (−50%) Mg in cells and had the greatest impact on the intrinsic element composition. The SC-ICP-TOF-MS shows the diversity of elemental content in single cells: for example, the P content under standard conditions varied between 12.4 and 890 fg cell–1. This technique allows studying both the uptake of elements and sublethal effects on physiology at a single-cell level.